Preparation method of porous fiber with nano cellulose fibril stable bubble structure

Through the porous fiber preparation method of stabilizing the bubble structure of nanocellulose filaments, the existing porous fibers have high production costs, complex processes and low mechanical strength, and the preparation of porous fibers with high strength and warmth performance has been achieved.

CN119411236AActive Publication Date: 2025-02-11DALIAN POLYTECHNIC UNIVERSITY

Patent Information

Application Number
CN202411618712.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-13
Publication Date
2025-02-11
Estimated Expiration
2044-11-13

AI Technical Summary

Technical Problem

The existing porous fibers are costly, complex in the production process, and low mechanical strength, resulting in the need of special care and insufficient durability in applications.

Method used

The method of preparing porous fibers with a stable bubble structure using nanocellulose filament. By mixing the nanocellulose filament dispersion with a polymer solution and a foaming additive, a bubble-type spinning solution is formed, and a wet spinning method is obtained. Porous fibers with internal closed-cell structure.

Benefits of technology

It realizes the preparation of porous fibers with simple process flow and low production cost, has high strength and unique internal closed-pore structure, which improves the warmth and functional modification possibilities of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119411236A_ABST
    Figure CN119411236A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a porous fiber with a nano cellulose fibril stable bubble structure. Comprising the following steps: adding a nanocellulose fibril dispersion liquid and a foaming aid into a polymer solution, mixing, and dispersing the mixed solution to obtain a spinning solution; injecting gas into the spinning solution, and stirring to obtain a bubble type spinning solution; the bubble type spinning solution is subjected to wet spinning to obtain the porous fiber. The nanocellulose fibrils have a diameter of 10 nm or less and a length of 500 nm or more. The porous fiber prepared by the method provided by the invention has an elliptical internal closed-pore structure and high strength. Compared with a traditional solid fiber, the porous fiber shows low volume density and heat conduction efficiency due to the existence of an internal closed-pore structure, so that the thermal insulation performance is better, and the internal closed-pore structure provides more possibilities for functional modification such as phase change capsule coating, nano-particle loading and medicine loading.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of fiber material engineering, and in particular to a method for preparing porous fibers having a stable bubble structure of nanocellulose fibrils. Background Art

[0002] Porous fiber is a fiber material containing a large number of pores, with remarkable characteristics such as high air permeability, low density, and excellent adsorption performance. Due to its unique structure and performance, it is widely used in building sound insulation, automotive interior, wound dressings, warm clothing, lightweight insulation materials and other fields. Although porous fiber is a material with great potential, the development and application of porous fiber still faces problems such as high production cost, complex process flow, and low mechanical strength. These problems lead to the fabrics or clothing made of porous fibers requiring special care, difficult processing, and insufficient durability in practical applications.

[0003] Therefore, there is an urgent need to develop a new closed-cell porous fiber material that is highly efficient in heat insulation, waterproof and lightweight, in order to overcome the above-mentioned problems of traditional porous fibers and promote the development of the fiber industry. Summary of the invention

[0004] In view of the shortcomings in the preparation and application of the above-mentioned porous fibers, the purpose of the present application is to provide a method for preparing porous fibers with a stable bubble structure of nanocellulose fibrils. The preparation method of the present application has a simple process flow, low production cost, and can achieve continuous preparation. The prepared porous fibers have a unique internal closed-cell structure and high strength.

[0005] The purpose of this application is achieved through the following technical solutions.

[0006] In a first aspect of the present application, a method for preparing a porous fiber having a nanocellulose fibril stable bubble structure is provided, comprising the following steps:

[0007] (1) adding a nanocellulose fibril dispersion and a foaming aid to the polymer solution and mixing the mixture, and subjecting the mixture to a dispersion treatment to obtain a spinning solution;

[0008] (2) injecting gas into the spinning solution and stirring to obtain a bubble-type spinning solution;

[0009] (3) The bubble-type spinning solution is wet-spun to obtain porous fibers.

[0010] In any embodiment of the present application, in step (1), the polymer is at least one of polyvinyl alcohol, chitosan, alginate, gelatin, agar, polyethylene oxide, polyacrylic acid, sodium polyacrylate, polyacrylamide, poly-N-isopropylacrylamide, etc. Among them, the average molecular weight of polyvinyl alcohol is between 60,000 and 90,000, the viscosity of chitosan is between 100 and 800 mPa·s, the alginate is sodium alginate, the average molecular weight of which is between 200,000 and 400,000, the average molecular weight of polyethylene oxide is between 10,000 and 100,000, the average molecular weight of sodium polyacrylate is between 4,000 and 5,000, the average molecular weight of polyacrylamide is between 10,000,000 and 20,000,000, and the average molecular weight of poly-N-isopropylacrylamide is between 20,000 and 50,000. The present application preferably uses a mixture of multiple polymers, such as the polymer of the present application is a mixture of three or four or five of polyvinyl alcohol, chitosan, alginate, gelatin, agar, polyethylene oxide, polyacrylic acid, sodium polyacrylate, polyacrylamide, and poly-N-isopropylacrylamide. In the case of a mixture of multiple polymers, the content relationship of each component is that the main polymer accounts for 60-90%, and the other polymers account for 10-40%, and the viscosity of the polymer solution finally obtained is in the range of 1000-10000 mPa·s. Among them, the main polymer can be polyvinyl alcohol, chitosan, alginate, gelatin, polyacrylic acid, etc., and the other polymers can be agar, polyethylene oxide, sodium polyacrylate, polyacrylamide, poly-N-isopropylacrylamide, etc.

[0011] In any embodiment of the present application, in step (1), the mass percentage concentration of the polymer in the polymer solution is 0.5 to 40%, preferably 1 to 30%.

[0012] In any embodiment of the present application, the polymer solution described in step (1) is prepared by adding a polymer and a co-solvent to deionized water and stirring and dissolving until the polymer is completely dissolved. The co-solvent is at least one of methanol, ethanol, isopropanol, aminoethanol, acetone, acetic acid, a surfactant, etc. The volume percentage concentration of the co-solvent in the polymer solution is 0.1 to 2%, preferably 0.5 to 1%. During the stirring and dissolving, the dissolution temperature is 30 to 99°C, preferably 35 to 95°C. During the stirring and dissolving, the dissolution time is 0.5 to 24h, preferably 1 to 12h. The dissolution time can be appropriately determined according to the dissolution state of the polymer, and the polymer can be stirred and dissolved until it is completely dissolved, that is, the polymer can be considered to be completely dissolved when the solution is stirred and dissolved until it is in a transparent liquid state.

[0013] In any embodiment of the present application, in step (1), the diameter of the nanocellulose fibrils is less than 10 nm and the length is more than 500 nm. Preferably, a high aspect ratio of the nanocellulose fibrils is adopted in the present application to ensure that the stability and viscosity of the nanocellulose fibrils in the spinning solution are improved, so that the bubbles can be retained in the spinning solution for a long time. If the aspect ratio of the nanocellulose fibrils is too small, the nanocellulose fibrils will not be able to play a skeletal support role. If the aspect ratio is too large, the viscosity of the spinning solution will be too high, thereby increasing the risk of clogging the spinneret during the spinning process, and also causing uneven fiber forming during the spinning process. Therefore, in the present application, the aspect ratio of the nanocellulose fibrils is set to between 40:1 and 3000:1, preferably between 40:1 and 2000:1.

[0014] In any embodiment of the present application, in step (1), the raw material of the nanocellulose fibrils is trees, plant straws, recycled clothing, etc., preferably trees and plant straws. In the present application, the nanocellulose fibrils of the specified size can be prepared by conventional methods in the art. It should be noted that the hydrophobically modified nanocellulose fibrils are not suitable for the present application even if their size meets the specified size of the present application due to their hydrophobicity.

[0015] In any embodiment of the present application, in step (1), the foaming aid is at least one of alkyl glycoside, fatty alcohol polyoxyethylene ether, lauryl amide propyl betaine, sodium dodecylbenzene sulfonate, sodium dodecyl sulfate, quaternary ammonium salt and the like.

[0016] In any embodiment of the present application, in step (1), the solid-liquid mass ratio of the polymer solution, the nanocellulose fibril dispersion and the foaming aid is 100:(3-60):(0-15), preferably 100:(5-60):(1-15).

[0017] In any embodiment of the present application, in step (1), the concentration of the nanocellulose fibril dispersion is 0.02 to 30%, preferably 0.1 to 25%.

[0018] In any embodiment of the present application, in step (1), the nanocellulose fibrils are added to deionized water and ultrasonically treated to obtain a nanocellulose fibril dispersion, wherein the ultrasonic treatment has an ultrasonic frequency of 5 to 100 kHz, a power range of 50 to 700 W, and a treatment time of 1 to 60 min, preferably 10 to 80 kHz, a power range of 100 to 600 W, and a treatment time of 5 to 60 min.

[0019] In any embodiment of the present application, in step (1), the dispersion treatment is ultrasonic treatment, in which the ultrasonic frequency is 5 to 100 kHz, the power range is 50 to 700 W, the treatment time is 1 to 60 min, preferably 10 to 80 kHz, the power range is 100 to 600 W, and the treatment time is 5 to 60 min.

[0020] In any embodiment of the present application, in step (1), a functional filler is further added to the polymer solution, and the functional filler is at least one of polyvinyl pyrrolidone, polyethylene imine, cationic starch, waterborne polyurethane, epichlorohydrin, polyamide epichlorohydrin, epoxy resin, sodium silicate, silicone resin, glutaraldehyde, carbon black, graphene, carbon nanotubes, paraffin, polyethylene glycol, nano zinc oxide, nano silver, nano titanium dioxide, nano silicon dioxide, fatty acid, etc. The solid-liquid mass ratio of the polymer solution, nanocellulose fibril dispersion, foaming aid and functional filler is 100: (3-60): (0-15): (0-15), preferably 100: (5-60): (1-15): (1-15). In the present application, adding an appropriate amount of functional filler can improve the properties of the porous fibrils, such as improving their mechanical strength, heat resistance, conductivity, heat storage capacity, photocatalytic effect, antibacterial property or other required functional properties. The type and amount of functional fillers added can be adjusted according to specific application scenarios to ensure the excellent performance of the porous fibers in different application scenarios.

[0021] In any embodiment of the present application, in step (2), the gas is at least one of nitrogen, carbon dioxide, helium, air, and argon.

[0022] In any embodiment of the present application, in step (2), during the stirring, the stirring speed is 1000 to 10000 rpm / min, and the treatment time is 1 to 90 min, preferably the stirring speed is 1500 to 10000 rpm / min, and the treatment time is 5 to 90 min.

[0023] In the present application, in the spinning solution obtained by step (1), the nanocellulose fibrils form a network structure, which can increase the stability and viscosity of the spinning solution, so that the bubbles can be retained in the spinning solution for a long time, and the fiber skeleton strength can also be improved. Furthermore, injecting gas into the spinning solution obtained in step (1) for foaming can reduce the penetration and escape of gas in the fiber and maintain the stability of the porous fiber morphology.

[0024] In any embodiment of the present application, in step (3), the bubble-type spinning solution is extruded into a coagulation bath through a spinneret, and the extruded fibers are coagulated in the coagulation bath to form spun fibers. The spun fibers obtained are subjected to a drawing treatment to increase the fiber strength, and then are appropriately washed to remove residual impurities, and are finally dried to obtain porous fibers.

[0025] In any embodiment of the present application, the pore size of the spinneret is 50 to 3000 μm, preferably 50 to 2000 μm, and the extrusion speed of the bubble-type spinning solution through the spinneret is 0.1 to 30 mL / min, preferably 0.5 to 30 mL / min.

[0026] In any embodiment of the present application, the coagulation bath is at least one of a saturated sodium sulfate solution, a sodium hydroxide solution, a calcium chloride solution, a methanol solution, an ethanol solution, a sodium hydroxide-ethanol solution, etc., the temperature of the coagulation bath is -30 to 50°C, preferably -20 to 50°C, and the coagulation time is 10 to 70s, preferably 20 to 70s. Among them, the methanol solution, ethanol solution, and sodium hydroxide-ethanol solution are low-temperature solution systems, wherein the low temperature is -30 to 10°C, preferably -20-5°C.

[0027] In any embodiment of the present application, in the drawing, the drawing ratio of the spun fiber is 2 to 10 times, preferably 4 to 10 times, and the drawing temperature is 25 to 200°C, preferably 30 to 200°C.

[0028] In any embodiment of the present application, in the washing, the stretched fiber is placed in a washing liquid for washing, wherein the washing liquid is at least one of deionized water, methanol, ethanol, and the like.

[0029] In any embodiment of the present application, in the drying, the washed fiber is dried at a drying temperature of 50 to 200° C., preferably 60 to 200° C., for a drying time of 1 to 20 min.

[0030] Beneficial effects of this application:

[0031] First, the spinning method of the present application has a simple process flow, low production cost, and can achieve continuous preparation, with high stability and repeatability. In addition, after appropriate adjustments to existing wet spinning equipment, the method can directly use these equipment to produce porous fibers, fully relying on existing production conditions and reducing additional equipment investment.

[0032] Secondly, the present application adopts nanocellulose fibrils with high aspect ratio, combined with the rich hydrogen bonding and electrostatic effects of nanocellulose fibrils, to form a stable three-dimensional physical network structure in the spinning solution. On the one hand, the viscosity and stability of the spinning solution are increased, the floating and dissipation of bubbles are prevented, and the bubbles are retained in the process of the transformation of the bubble-type spinning solution to porous fibers; on the other hand, the nanocellulose fibrils with high aspect ratio improve the dispersibility of each component in the spinning solution, ensuring the uniformity during the spinning process. In addition, the high aspect ratio and rich hydroxyl groups of the nanocellulose fibrils are conducive to enhancing the interaction between polymer molecular chains, avoiding the phenomenon of non-coagulation and low strength during the primary fiber molding process, improving the fiber coagulation molding ability, and making the obtained fiber have better pore size stability and mechanical strength. Further, in the spinning solution containing the three-dimensional physical network structure of nanocellulose fibrils, gas is injected for foaming, which reduces the penetration and escape of gas in the fiber and maintains the stability of the porous fiber morphology.

[0033] The porous fiber prepared by the method of the present application has an elliptical internal closed-cell structure and high strength. Compared with traditional solid fibers, the porous fiber of the present application exhibits lower volume density and heat conduction efficiency due to the presence of the internal closed-cell structure, thereby having better warmth retention performance. In addition, the porous fiber of the present application provides more possibilities for functional modification such as phase change capsule coating, nanoparticle loading, and drug loading due to its unique internal closed-cell structure. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 This is the SEM image of the porous fiber with a stable bubble structure of nanocellulose fibrils in Example 1.

[0035] Figure 2 This is the stress-strain curve of the porous fiber with a stable bubble structure of nanocellulose fibrils in Example 1.

[0036] Figure 3 This is the SEM image of the porous fiber with a stable bubble structure of nanocellulose fibrils in Example 2.

[0037] Figure 4 This is the stress-strain curve of the porous fiber with a stable bubble structure of nanocellulose fibrils in Example 2.

[0038] Figure 5 This is the SEM image of the porous fiber with a stable bubble structure of nanocellulose fibrils in Example 3.

[0039] Figure 6 This is the stress-strain curve of the porous fiber with a stable bubble structure of nanocellulose fibrils in Example 3.

[0040] Figure 7This is the DSC graph of the porous fiber with a stable bubble structure of nanocellulose fibrils in Example 3. DETAILED DESCRIPTION

[0041] In order to make the technical solution of the present application clearer, the present application is further described in detail below in conjunction with the accompanying drawings and embodiments. The specific embodiments described here are only used to explain the present application and are not used to limit the present application.

[0042] In the following examples, unless otherwise specified, the experimental methods used are all conventional methods, and the reagents used can be purchased from chemical or biological reagent companies.

[0043] Materials used in the following examples:

[0044] Nanocellulose fibrils: Derived from trees or straw, with a diameter of 4 to 10 nm and a length of 500 to 2000 nm, they are prepared using conventional methods in the art.

[0045] Polyvinyl alcohol: average molecular weight: 76000, model P: 1799, manufacturer: Shanghai Aladdin Biochemical Technology Co., Ltd.;

[0046] Chitosan: viscosity: 200-600 mPa·s, manufacturer: Sinopharm Chemical Reagent Co., Ltd.;

[0047] Polyacrylic acid: viscosity: ≤2000mPa·s, manufacturer: Shanghai Aladdin Biochemical Technology Co., Ltd.;

[0048] Polyacrylamide: average molecular weight: 15,000,000, manufacturer: Shanghai Aladdin Biochemical Technology Co., Ltd.;

[0049] Poly (N-isopropylacrylamide): average molecular weight: 40,000, manufacturer: Shanghai Aladdin Biochemical Technology Co., Ltd.;

[0050] Sodium polyacrylate: average molecular weight: 5100, manufacturer: Shanghai Aladdin Biochemical Technology Co., Ltd.;

[0051] Sodium alginate: average molecular weight: 300000, manufacturer: Qingdao Mingyue Seaweed Group Co., Ltd.

[0052] Polyethylene oxide: average molecular weight: 100,000, manufacturer: Sinopharm Chemical Reagent Co., Ltd.

[0053] Example 1

[0054] 1. Preparation of polymer solution: Deionized water, polyvinyl alcohol, chitosan, polyacrylic acid, polyacrylamide, and acetic acid were mixed in a ratio of 790 mL, 150 g, 40 g, 5 g, 5 g, and 10 mL, and stirred at 95 ° C for 3 h to completely dissolve the polymer to obtain a polymer solution with a mass percentage concentration of 20%.

[0055] 2. Preparation of spinning solution: Add an appropriate amount of nanocellulose fibrils (diameter of 10nm, length of 600nm) into deionized water, and ultrasonically disperse for 10 minutes to obtain a nanocellulose fibril dispersion with a mass percentage concentration of 10%. Deionized water, the above polymer solution, the nanocellulose fibril dispersion after ultrasonic dispersion, alkyl glycoside, fatty alcohol polyoxyethylene ether, epichlorohydrin, and nano zinc oxide are mixed in a ratio of 230mL, 650g, 100g, 5g, 5g, 5g, and ultrasonically dispersed for 30 minutes to obtain a spinning solution with a concentration of 16%. Among them, in the ultrasonic dispersion treatment, the ultrasonic frequency used is 60kHz, and the ultrasonic power range is 300W. The concentration of the spinning solution refers to the mass percentage concentration of all substances in the spinning solution except water in the total mass.

[0056] 3. Foaming treatment of the spinning solution: The spinning solution was placed in a glove box, and nitrogen was introduced for 30 minutes to exhaust the air. Then, the spinning solution was stirred while continuing to introduce nitrogen to obtain a bubble-type spinning solution, wherein the stirring speed was 8000 rpm / min and the stirring time was 30 minutes.

[0057] 4. Preparation of composite porous fibers: The bubble-type spinning solution is placed in a spinning barrel for wet spinning. Specifically, the bubble-type spinning solution is extruded through a porous spinneret into a coagulation bath for coagulation to obtain nascent fibers. The nascent fibers are stretched, washed, and dried to obtain porous fibers with a stable bubble structure of nanocellulose fibrils. The spinneret aperture is 600 μm, the extrusion speed is 10 mL / min, the coagulation bath is a 2% sodium hydroxide ethanol solution, the coagulation bath temperature is -10°C, and the coagulation time is 60s; the draft ratio of the nascent fiber is 4 times, the draft temperature is 30°C, the washing liquid is deionized water, the drying temperature is 90°C, and the drying time is 5 min.

[0058] Example 2

[0059] 1. Preparation of polymer solution: Deionized water, polyvinyl alcohol, sodium polyacrylate, polyacrylamide, poly (N-isopropyl acryloyl) and acetone were mixed in a ratio of 780 mL, 160 g, 20 g, 15 g, 5 g and 20 g, and stirred at 95 ° C for 2 h to completely dissolve the polymer to obtain a polymer solution with a polymer concentration of 20% (m / m).

[0060] 2. Preparation of spinning solution: Add an appropriate amount of nanocellulose fibrils (diameter of 8nm, length of 800nm) into deionized water, and ultrasonically disperse for 15min to obtain nanocellulose fibrils with a mass percentage concentration of 12%. Deionized water, the above polymer solution, the nanocellulose fibril dispersion after ultrasonic dispersion, sodium lauryl sulfate, quaternary ammonium salt, nano titanium dioxide, and nano silicon dioxide are mixed in a ratio of 300mL, 600g, 50g, 5g, 5g, 20g, and 20g, and ultrasonically disperse for 30min to obtain a spinning solution with a concentration of 17.6%. In the ultrasonic dispersion, the ultrasonic frequency used is 40kHz and the ultrasonic power range is 500W.

[0061] 3. Foaming treatment of the spinning solution: The spinning solution was placed in a glove box and air was introduced for 5 minutes. The spinning solution was then stirred while continuing to introduce air to obtain a bubble-type spinning solution, wherein the stirring speed was 6000 rpm / min and the stirring time was 50 minutes.

[0062] 4. Preparation of composite porous fibers: The bubble-type spinning solution is placed in a spinning barrel for wet spinning. Specifically, the bubble-type spinning solution is extruded through a porous spinneret into a coagulation bath for coagulation to obtain primary fibers. The primary fibers are stretched, washed, and dried to obtain porous fibers with a stable bubble structure of nanocellulose fibrils. The spinneret aperture is 800 μm, the extrusion speed is 15 mL / min, the coagulation bath is a saturated sodium sulfate solution, the coagulation bath temperature is 25°C, and the coagulation time is 120s; the stretching ratio is 5 times, the stretching temperature is 50°C, the washing liquid is deionized water, the drying temperature is 110°C, and the drying time is 3min.

[0063] Example 3

[0064] 1. Preparation of polymer solution: Deionized water, polyvinyl alcohol, sodium alginate, gelatin, polyethylene oxide, and sodium polyacrylate were mixed in a ratio of 800 mL, 170 g, 10 g, 10 g, 5 g, and 5 g, and stirred at 90 ° C for 3 h to completely dissolve the polymer to obtain a polymer solution with a polymer concentration of 20% (m / m).

[0065] 2. Preparation of spinning solution: Add an appropriate amount of nanocellulose fibrils (diameter of 5nm, length of 1000nm) into deionized water, and perform ultrasonic dispersion treatment for 5min to obtain a nanocellulose fibril dispersion with a mass percentage concentration of 8%. Deionized water, the above polymer solution, the nanocellulose fibril dispersion after ultrasonic dispersion, alkyl glycoside, fatty alcohol polyoxyethylene ether, glutaraldehyde, and paraffin are mixed in a ratio of 160mL, 600g, 200g, 5g, 5g, 10g, and 20g, and then perform ultrasonic dispersion treatment for 40min to obtain a spinning solution with a concentration of 17.6%. In the ultrasonic dispersion treatment, the ultrasonic frequency used is 40kHz and the ultrasonic power range is 500W.

[0066] 3. Foaming treatment of the spinning solution: The spinning solution was placed in a glove box and carbon dioxide was introduced for 30 minutes to exhaust the air. The spinning solution was then stirred while continuing to introduce carbon dioxide to obtain a bubble-type spinning solution. The stirring speed was 7000 rpm / min and the foaming time was 40 minutes.

[0067] 4. Preparation of composite porous fibers: Place the bubble-type spinning solution in a spinning barrel for wet spinning. Specifically, extrude the bubble-type spinning solution through a porous spinneret into a coagulation bath for coagulation to obtain primary fibers. The primary fibers are stretched, washed, and dried to obtain porous fibers with a stable bubble structure of nanocellulose fibrils. The spinneret aperture is 500 μm, the extrusion speed is 5 mL / min, the coagulation bath is a 6% calcium chloride aqueous solution, the coagulation bath temperature is 0°C, and the coagulation time is 60s; the stretching ratio is 5 times, the stretching temperature is 50°C, the washing liquid is deionized water, the drying temperature is 100°C, and the drying time is 10min.

[0068] Example 4

[0069] Figure 1 to Figure 7 The physical structure, mechanical properties and functional test results of the porous fibers obtained according to Examples 1 to 3 are shown in FIG.

[0070] Figure 1 This is a SEM image of the oblique section of the porous fiber with a stable bubble structure of nanocellulose fibrils in Example 1. Figure 1 It can be seen that through the analysis of the porous fiber structure, a large number of closed-cell structures are found inside it, and the pores in the fiber present closed elliptical holes (indicated by arrows), with a pore width of 20 to 35 μm and a length of 50 to 65 μm. The overall structure of the porous fiber is complete, which effectively ensures the lightweight and thermal insulation performance of the porous material.

[0071] Figure 2 is the stress-strain curve of the porous fiber with stable bubble structure of nanocellulose fibrils in Example 1. Figure 2 It can be seen that when the stress reaches 49.2MPa, the porous fiber breaks with an elongation at break of 6.3%, which shows good mechanical properties.

[0072] Figure 3 This is a SEM image of the oblique section of the porous fiber with a stable bubble structure of nanocellulose fibrils in Example 2. Figure 3 It can be seen that through the analysis of the porous fiber structure, a large number of closed-cell structures are found inside it. The pores in the fiber present closed elliptical holes (indicated by arrows), with a pore width of 25 to 40 μm and a length of 50 to 70 μm. The overall structure of the porous fiber is complete, which effectively ensures the lightweight and thermal insulation performance of the porous material.

[0073] Figure 4 is the stress-strain curve of the porous fiber with stable bubble structure of nanocellulose fibrils in Example 2. Figure 4 It can be seen that when the stress reaches 40.5MPa, the porous fiber breaks with an elongation at break of 11%, which shows good mechanical properties.

[0074] Figure 5 This is a SEM image of the oblique section of the porous fiber with a stable bubble structure of nanocellulose fibrils in Example 3. Figure 3 It can be seen that through the analysis of the porous fiber structure, a large number of closed-cell structures are found inside it. The pores in the fiber present closed elliptical holes (indicated by arrows), with a pore width of 20 to 40 μm and a length of 50 to 70 μm. The overall structure of the porous fiber is complete, which effectively ensures the lightweight and thermal insulation performance of the porous material.

[0075] Figure 6 is the stress-strain curve of the porous fiber with stable bubble structure of nanocellulose fibrils in Example 3. Figure 6 It can be seen that when the stress reaches 28.2MPa, the porous fiber breaks and the elongation at break is 5.1%.

[0076] Figure 7 The DSC diagram of the porous fiber with stable bubble structure of nanocellulose fibrils in Example 3 is shown in FIG. Figure 4It can be seen that the melting peak of paraffin in the composite porous fiber is at 29.3°C, and the melting enthalpy is 9.14 J / g. The composite porous fiber of the present application has a higher melting enthalpy, which indicates that it has a superior ability to store phase change particles. In addition, the unique closed elliptical pore structure of the composite porous fiber further enhances its heat storage and thermal insulation properties. These pore structures not only help to effectively seal the phase change material, but also provide the fiber with better thermal management capabilities, making it perform well in warmth preservation. This advantage makes the composite porous fiber more potential than traditional phase change fibers in thermal energy storage and temperature regulation applications.

Claims

1. A method for preparing porous fibers having a stable bubble structure of nanocellulose fibrils, characterized in that: The steps include: (1) adding a nanocellulose fibril dispersion and a foaming aid into a polymer solution and mixing the mixture, and subjecting the mixture to a dispersion treatment to obtain a spinning solution; (2) injecting gas into the spinning solution and stirring to obtain a bubble-type spinning solution; (3) The bubble-type spinning solution is wet-spun to obtain porous fibers.

2. The preparation method according to claim 1, characterized in that: In step (1), The polymer in the polymer solution is at least one of polyvinyl alcohol, chitosan, alginate, gelatin, agar, polyethylene oxide, polyacrylic acid, sodium polyacrylate, polyacrylamide, and poly-N-isopropylacrylamide; and / or, The mass percentage concentration of the polymer in the polymer solution is 0.5-40%.

3. The preparation method according to claim 1, characterized in that: The polymer solution described in step (1) is prepared by adding a polymer and a co-solvent into deionized water and stirring and dissolving the polymer until the polymer is completely dissolved.

4. The preparation method according to claim 3, characterized in that The cosolvent is at least one of methanol, ethanol, isopropanol, aminoethanol, acetone, formic acid, acetic acid, and a surfactant; and / or, The volume percentage concentration of the co-solvent in the polymer solution is 0.1-2%; and / or, During the stirring and dissolving, the dissolving temperature is 30 to 99° C.; and / or, During the stirring and dissolving, the dissolving time is 0.5 to 24 hours.

5. The preparation method according to claim 1, characterized in that: In step (1), the diameter of the nanocellulose fibrils is less than 10 nm and the length is more than 500 nm.

6. The preparation method according to claim 1, characterized in that: In step (1) The raw materials of the nanocellulose fibrils are trees, plant straws, and recycled clothing; and / or, The foaming aid is at least one of alkyl glucosides, fatty alcohol polyoxyethylene ethers, lauryl amide propyl betaine, sodium dodecylbenzene sulfonate, sodium dodecyl sulfate, and quaternary ammonium salts; and / or, The solid-liquid mass ratio of the polymer solution, the nanocellulose fibril dispersion and the foaming aid is 100:(3-60):(0-15); and / or, The mass concentration of the nanocellulose fibrils in the nanocellulose fibril dispersion is 0.02 to 30%; and / or, Adding the nanocellulose fibrils into deionized water and performing ultrasonic treatment to obtain a nanocellulose fibril dispersion, wherein the ultrasonic treatment has an ultrasonic frequency of 5 to 100 kHz, a power of 50 to 700 W, and a treatment time of 1 to 60 min; and / or, The dispersion treatment is ultrasonic treatment, in which the ultrasonic frequency is 5 to 100 kHz, the power is 50 to 700 W, and the treatment time is 1 to 60 min.

7. The preparation method according to claim 1, characterized in that: In step (1), a functional filler is further added to the polymer solution, and the functional filler is at least one of polyvinyl pyrrolidone, polyethylene imine, cationic starch, waterborne polyurethane, epichlorohydrin, polyamide epichlorohydrin, epoxy resin, sodium silicate, silicone resin, glutaraldehyde, carbon black, graphene, carbon nanotubes, paraffin, polyethylene glycol, nano zinc oxide, nano silver, nano titanium dioxide, nano silicon dioxide, and fatty acid; the solid-liquid mass ratio of the polymer solution, nano cellulose fibril dispersion, foaming aid and functional filler is 100:(3-60):(0-15):(0-15).

8. The preparation method according to claim 1, characterized in that: In step (2), The gas is at least one of nitrogen, carbon dioxide, helium, air and argon; and / or, During the stirring, the stirring speed is 1000-10000 rpm / min, and the processing time is 1-90 min.

9. The preparation method according to claim 1, characterized in that: In step (3), the wet spinning comprises the following steps: extruding the bubble-type spinning solution through a spinneret into a coagulation bath, allowing the extruded fibers to coagulate in the coagulation bath to form nascent fibers, and the nascent fibers become porous fibers after being drawn, washed and dried.

10. The preparation method according to claim 8, characterized in that: The pore size of the spinneret is 50 to 3000 μm, and the extrusion speed of the bubble-type spinning solution through the spinneret is 0.1 to 30 mL / min; and / or, The coagulation bath is at least one of a saturated sodium sulfate solution, a sodium hydroxide solution, a calcium chloride solution, a methanol solution, an ethanol solution, a sodium hydroxide-ethanol solution, etc., the temperature of the coagulation bath is -30 to 50° C., and the coagulation time is 10 to 70 seconds; and / or, In the drawing, the drawing ratio of the as-spun fiber is 2 to 10 times, and the drawing temperature is 25 to 200° C.; and / or, In the washing, the stretched fiber is placed in a washing liquid for washing, wherein the washing liquid is at least one of deionized water, methanol, and ethanol; and / or, In the drying, the washed fiber is dried at a drying temperature of 50 to 200° C. and a drying time of 1 to 20 minutes.

Citation Information

Patent Citations

  • Plant fiber porous composite material

    CN103772749A

  • A cellular solid material drug carrier comprising cellulose nanofibers (CNF) wherein the cellular solid material comprises closed cells

    CN109641061A

  • Super-tough cellulose aerogel fiber as well as preparation method and application thereof

    CN116791225A

  • Micro porous synthetic fiber and method ofmanufacturing for the same

    KR100667626B1

  • Process for forming improved foamed fibers

    US4753762A

Cited By

  • Supercritical lightweight fabric and production method thereof

    CN120797290A